Becoming Occupation-Based: A Case Study. Issue 4 (2nd October 2014) - Skubik-Peplaski, Camille; Howell, Dana; Harrison, Anne
ABSTRACT This descriptive case study illustrates the experiences of a 55-year-old male with a chronic disability resulting from a stroke, living in the community and a clinician's trial using occupation-based interventions predominately in a rehabilitation setting. The participant engaged in occupation-based interventions three times a week for 5 weeks guided by the Canadian Occupational Performance Measure (COPM). Data were collected through semi-structured interviews during the intervention sessions and journal entries made by the therapist. Results suggested occupation-based interventions facilitated a transformation for both the client and the therapist by enhancing the participant's occupational performance and the ability to resume previous roles. The therapist's belief in the power and value of occupation-based practice was reinforced and validated, particularly in the rehabilitation of an individual with chronic stroke.